Measurement of Hip Contact Pressure During Arthroscopic Femoroacetabular Impingement Surgery - Kaya, Mitsunori (Arthrosc Tech, 2017)
Cam impingement is caused by jamming of an abnormal femoral head with an increased radius into the acetabulum during motion. Therefore, the elevation of the contact pressure during the motion is suspected to be an essential pathology of femoroacetabular impingement. However, there is no method to quantify the hip contact pressure during motion. The purpose of this Technical Note is to introduce a technique to measure the hip contact pressure during arthroscopic surgery. The author believes that the current technique will be a useful tool for the detailed investigation of the pathophysiology femoroacetabular impingement and thorough evaluation of its therapeutic significance.